Revisiting the tautology problem in rational choice theory: What it is and how to move forward theoretically and empirically - Steinmetz, Kevin F. (European journal of criminology, 2024)
Criminological rational choice theory is blighted by tautology?that if a crime occurs, then by definition the benefits must exceed the costs. The current analysis details the nature of this tautology as well as its theoretical and philosophical implications concerning the circumstances under which offenders make rational (thoughtful and reflective) or irrational (habitual, intuitive, or instinctual) choices. In short, rational choice theorists appear to side-step the problems presented by this tautology by attempting to coerce observations and theorizing to conform with assumptions about cost?benefit rationality. This essay concludes by setting forth an agenda for the continued empirical investigation of the rational choice perspective?one where the perceived cost/benefit analysis itself for criminal behavior is treated as the outcome of interest.